Iron–PNP‐Pincer‐Catalyzed Transfer Dehydrogenation of Secondary Alcohols. Issue 13 (4th July 2019) - Budweg, Svenja; Wei, Zhihong; Jiao, Haijun; Junge, Kathrin; Beller, Matthias
Abstract: Invited for this month's cover is the group of Matthias Beller at the Leibniz‐Institute for Catalysis in Rostock. The image illustrates the catalytic dehydrogenation of secondary alcohols to the corresponding ketones using iron‐based pincer complexes. The Communication itself is available at 10.1002/cssc.201900308 . Abstract : "The horseshoe represents an iron‐based pincer catalyst…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.201900308 . View the Front Cover here: 10.1002/cssc.201901645 .